QFD Based Benchmarking Logic Using TOPSIS and Suitability Index. (27th September 2015) - Cho, Jaeho; Chun, Jaeyoul; Kim, Inhan; Choi, Jungsik
Abstract : Users' satisfaction on quality is a key that leads successful completion of the project in relation to decision-making issues in building design solutions. This study proposed QFD (quality function deployment) based benchmarking logic of market products for building envelope solutions. Benchmarking logic is composed of QFD-TOPSIS and QFD-SI. QFD-TOPSIS assessment model is able to evaluate users' preferences on building envelope solutions that are distributed in the market and may allow quick achievement of knowledge. TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) provides performance improvement criteria that help defining users' target performance criteria. SI (Suitability Index) allows analysis on suitability of the building envelope solution based on users' required performance criteria. In Stage 1 of the case study, QFD-TOPSIS was used to benchmark the performance criteria of market envelope products. In Stage 2, a QFD-SI assessment was performed after setting user performance targets. The results of this study contribute to confirming the feasibility of QFD based benchmarking in the field of Building Envelope Performance Assessment (BEPA).